Sistem Nilai dengan Bobot Komponen yang Dinamis Studi Kasus Binus Internasional - Karto Iskandar (Bina Nusantara University, 2011)
Every institution must have an assessment system to determine the graduation of the students. Commonly universities implement static scoring systems to simplify the counting and operational process. Similarly, Bina Nusantara University implements a static scoring system. Along with the development of business models, the need for cooperation with foreign universities and quality improvement, Binus International requires a dynamic component scoring which results in changes in database design and information systems. This research uses literary study, database designing and system designing. This research aims to analyze and design a database and a scoring system at Binus International in order to support the assessment process with a dynamic component scoring. The results are a design of a dynamic scoring system. It can be concluded that the scoring system with dynamic value components is more suitable for Binus International. For further development the scoring systems is expected to be created using the online scoring data collection by the lecturers with a simpler process that considers the encription element.